Simulation of the loss-cone instability in spherical systems: I. Dominating harmonic potential - Polyachenko, Evgeny V.; Berczik, Peter; Just, Andreas (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. A new so-called ‘gravitational loss-cone instability’ in stellar systems has recently been investigated theoretically in the framework of linear pert
Advance access publication 2019 December 20
Gesehen am 17.02.2020